2018
DOI: 10.1093/jhps/hny034
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous pigmented villonodular synovitis and synovial chondromatosis of the hip: case report

Abstract: This report presents a case of a 37-year-old female with a history of hip pain. Magnetic resonance arthrography revealed loose bodies within the joint and synovial hypertrophy indicative of synovial chondromatosis (SC). Hip arthroscopy revealed free chondral bodies and focal villonodular synovial proliferation. The focal synovial proliferation was excised, a total synovectomy performed, and all cartilaginous free bodies removed. A post-operative histological examination of the removed nodular mass and synovium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…8 The molecular background is still uncertain, but the disease is thought to originate from a metaplastic variation of synovial cells into a cartilaginous tissue. 9 A cytogenic study of large joints with SC revealed consistent abnormalities within chromosome 6, that suggested a neoplastic origin. 9 However, no genetic correlation has been made in current literature related to TMJ SC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The molecular background is still uncertain, but the disease is thought to originate from a metaplastic variation of synovial cells into a cartilaginous tissue. 9 A cytogenic study of large joints with SC revealed consistent abnormalities within chromosome 6, that suggested a neoplastic origin. 9 However, no genetic correlation has been made in current literature related to TMJ SC.…”
Section: Discussionmentioning
confidence: 99%
“…9 A cytogenic study of large joints with SC revealed consistent abnormalities within chromosome 6, that suggested a neoplastic origin. 9 However, no genetic correlation has been made in current literature related to TMJ SC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the literature is basically in the form of case reports. The minimum age of synovial chondromatosis reported at present is 2 years old [ 5 ], but there are few reports of SC complications Ben Efrima reported a 37 year old female hip joint SC with pigmented villonodular synovitis [ 6 ], Jones reported 2 cases of SC with peripheral nerve compression [ 7 ], Monestier reported 2 cases of foot fat deposition combined with SC [ 8 ]. However, no case of knee synovial chondromatosis combined with tuberculosis has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the joint surfaces can result in secondary degenerative joint disease. 1,8,12,13,14 , as well as smaller lesions in the left shoulder (Fig. 1) , Corresponding Author: Felix Osuna Gutierrez Therefore, it was decided to perform a positron emission tomography, finding significant occupation of the joint (Fig 1).…”
Section: Clinical Casementioning
confidence: 99%